2023
DOI: 10.3389/fgene.2023.1087432
|View full text |Cite
|
Sign up to set email alerts
|

Delineating intra-tumoral heterogeneity and tumor evolution in breast cancer using precision-based approaches

Kutlwano Rekgopetswe Xulu,
Ekene Emmanuel Nweke,
Tanya Nadine Augustine

Abstract: The burden of breast cancer continues to increase worldwide as it remains the most diagnosed tumor in females and the second leading cause of cancer-related deaths. Breast cancer is a heterogeneous disease characterized by different subtypes which are driven by aberrations in key genes such as BRCA1 and BRCA2, and hormone receptors. However, even within each subtype, heterogeneity that is driven by underlying evolutionary mechanisms is suggested to underlie poor response to therapy, variance in disease progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 190 publications
0
4
0
Order By: Relevance
“…It’s also important to take in account variation of evolution within tumour sub-populations 102 . As mutational pathways would also vary with the different challenges present in the tumour microenvironment and a cancer’s strategy can differ in response to this environment 103 . For example, in the tumours of the Devil Facial Tumour Disease, B2M is downregulated in order to evade detection by the immune system 104 .…”
Section: Discussionmentioning
confidence: 99%
“…It’s also important to take in account variation of evolution within tumour sub-populations 102 . As mutational pathways would also vary with the different challenges present in the tumour microenvironment and a cancer’s strategy can differ in response to this environment 103 . For example, in the tumours of the Devil Facial Tumour Disease, B2M is downregulated in order to evade detection by the immune system 104 .…”
Section: Discussionmentioning
confidence: 99%
“…The development of many tumors starts at the cell level through a process of somatic mutation that causes genetic variation/instability and arises through natural selection which acts as purifying selection that eliminates the deleterious mutations, or as positive selection, which maintains the functionally advantageous mutations, which allow, from a neoplastic perspective, aberrant proliferation, invasion, and metastasis [28][29][30]. Most tumoral clones share genomic rearrangements and cancer driver gene mutations, illustrating that such events may occur early in the cancer evolutionary process [31]. However, Ostrow et al (2014) showed that the cancer evolutionary process, dominated by positive selection of somatic mutations at a cell level, differs from organism's evolution, which is dominated by purifying selection affecting germline (hereditary) mutations at organismal level [29].…”
Section: Bc Is a Genomic Diseasementioning
confidence: 99%
“…Therapeutic approaches, such as immune checkpoint inhibitors (ICIs), adoptive cell therapies, and therapeutic vaccines, aim to bolster the immune response against cancer cells, including CTCs [145]. The success of immunotherapy against CTCs hinges on factors, such as CTC immunogenicity, antigen expression, and the immune system's capacity to recognize and eliminate these cells [146]. The TME, replete with immune-suppressive elements, further modulates the efficacy of immunotherapies against CTCs [147].…”
Section: The Complex Interplay Between Immune Dynamics and Ctcs In Br...mentioning
confidence: 99%